Systems Approach in Tobacco Dependence Treatment through Hospitals. (December 2018) - Gupta, Rakesh; Narake, Sameer
This study on systems approach in tobacco dependence treatment was done to (a) Assess the feasibility of tobacco treatment protocol (TTP), (b) Assess quit rate among those treated with TTP vs. no treatment and (c) Compare treatment outcome in Brief Intervention (BI) and Intensive Intervention (II) with or without pharmacotherapy. This one year study (2013), undertaken at a hospital at Jaipur, India identified currently tobacco-using patients. Those willing were assisted to quit through brief intervention (BI) or intensive treatment (II). All were followed-up telephonically for one year. The responders were categorized as successful quit, failed to quit and relapsed. This study enrolled 1264 patients out of 19657 (6.43%). In 43.4 per cent patients (549/1264) who consented for the treatment, the overall quit rate was 26.1 per cent (CI: 23.8 -28.6) whereas in those treated with BI and II were 54.2 per cent (CI: 49.7 -59.0) and 84.9 per cent (CI: 78.4 -92.0) respectively vs. zero quit rate in untreated. The use of pharmacotherapy improved overall quit rate by 14.6 per cent. The quit rates did not differ for the type of tobacco used. Since, this study could achieve its objective of implementing the systems approach in tobacco treatment protocol in a hospital-setting, it merits a replication.